Combined intense pulsed light and Er:YAG laser treatment of congenital melanocytic nevus. (June 2015) - Lee, Ji Min; Kim, Il-Hwan; Rhyu, Im Joo; Ryu, Hwa Jung
Abstract: Congenital melanocytic nevi (CMN) are benign nevomelanocytic proliferations that are present at birth. CMN are commonly classified according to their size and the management of CMN is diverse, including excision, dermabrasion and laser treatment. Several studies have shown the effectiveness of laser therapy for CMN in cosmetically sensitive and anatomically critical areas. In the present case, combination treatment with intense pulsed light (IPL) and erbium:yttrium-aluminum-garnet (Er:YAG) laser was used, and its effectiveness was evaluated. A 56-year-old man with a CMN on the left malar area was treated with combined IPL and Er:YAG laser treatment once monthly. After ten sessions of treatment, the lesion showed improvement leaving only a grayish hue. Thus, we report a case of CMN on face that was successfully treated with combined IPL and Er:YAG laser treatment.